Rosyjscy emigranci w miniaturach satyrycznych Arkadija Awierczenki - Bielniak, Nel (Studia Rossica Posnaniensia, 2020)
The transformations in Russian satirical literature conditioned by the difficult emigration situation were reflected in the works of Arkady Averchenko, one of the most significant satirists of pre-revolutionary Russia. In his short stories created in exile, the writer showed the problems and dilemmas that his fellow-countrymen had to face abroad, mainly in Constantinople and Prague. The feeling of homelessness, loneliness and uprooting that accompanied the emigrants constantly intensified the need for self-identification in a foreign culture, which was demonstrated in manifesting their national distinctiveness, confronting new customs and idealizing the Russian past. By immortalizing the mood, spiritual life and living conditions as well as a specific metamorphosis of Russian emigrants, Averchenko did not forget about their vices. Therefore, the short stories of the emigration period, in which the writer willingly combined elements of comedy and tragedy, were saturated with self-irony, pain and bitter reflection, skillfully hidden under the mask of humour and satire.